Manufacturing process quality tracking and early warning system for building material equipment group enterprise considering schedule. (14th June 2023) - Xu, Wenxiang; Wang, Lei; Zuo, Ying
Since it is difficult for building material equipment group enterprise to track quality information and provide reasonable early warning for quality problems, a collaborative quality tracking and early warning method was developed. Firstly, a framework of multi-level quality information tracking and quality problem early warning considering schedule was established. Secondly, a multi-source information intergration framework was proposed in this study, and an interaction method of heterogeneous data based on intermediate object model for the framework was designed. Then, to describe the type and emergency degree of a quality problem comprehensively, a classification priority early warning method considering the schedule of manufacturing task was proposed in this research. Finally, a typical case was presented by using the model and method proposed in this study, and a quality dynamic tracking and early warning system was designed and developed.